« Nous sommes des sans-droits ». La nécropolitique du VIH pour les sans-papiers en Belgique - Charlotte Pezeril (L’Année du Maghreb)
This article aims to analyze the contemporary effectiveness of bio-legitimacy as defined by Fassin in 2001, which allows sick people to stay in Europe if they cannot be treated in their own country. Based on a survey studying HIV-related discrimination complaints received at Unia (Pezeril, 2017), the Belgian Centre for Equal Opportunities and the Fight against Discrimination, three anthropological figures are identified in order to stress the emblematic trajectories of undocumented migrants with HIV coming from the Maghreb to Belgium. The figures of Ahmed, Djamila and Saïd refer to ideal-typical trajectories, linked to the sexual, gendered and criminalized history of HIV, which are deeply shaped by migration policies, and by regularization, asylum and expulsion practices. Ahmed’s story shows how the HIV diagnosis complicates an already difficult situation of homosexuality which is partly hidden. Restrictions on regularization based on health status will prevent him from being legally established in the country. The second figure, Djamila, refers to the gendered history of HIV insofar as it finds its root in a conflictual relation with a man and in sexual violence. In this case, HIV is felt as being the least of her problems. Rather, she is preoccupied by her legal situation, as she cannot claim the right to stay in Europe without returning with and cohabitating with this abusive man. Finally, in the case of Saïd, HIV is grasped through his criminal history. His situation is typical of the double punishment encountered by foreigners who are incarcerated for petty offences or for having been arrested without adequate administrative documents. We may even analyse his situation as a triple punishment since transmitting HIV or exposing oneself to the illness has recently been criminalized. Thus, the restriction of European migration policies today is akin to a necropolitics which creates a world of people with no rights. And ultimately, as Achille Mbembe’s calls it (2006), a world of “living deads”.